ENHANCING LANGUAGE SKILL DEVELOPMENT THROUGH TASK-BASED LANGUAGE TEACHING (TBLT) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Task-Based Language Teaching (TBLT) has gained attention as an effective, learner-centered approach that promotes language skill development through meaningful, real-life tasks. This article explores the principles of TBLT, its applications for enhancing the four core language skills (listening, speaking, reading, and writing), and insights on integrating TBLT for comprehensive language proficiency. By examining key components and research-backed benefits of TBLT, this article highlights the approach's potential to foster authentic language use and improve learners’ confidence, fluency, and critical skills for real-world communication.